From Bedside to the Bench—A Call for Novel Approaches to Prognostic Evaluation and Treatment of Empyema - Karandashova, Sophia; Florova, Galina; Idell, Steven; Komissarov, Andrey A. (Frontiers in Pharmacology, 2022)
Empyema, a severe complication of pneumonia, trauma, and surgery is characterized by fibrinopurulent effusions and loculations that can result in lung restriction and resistance to drainage. For decades, efforts have been focused on finding a universal treatment that could be applied to all patients with practice recommendations varying between intrapleural fibrinolytic therapy (IPFT) and surgical drainage. However, despite medical advances, the incidence of empyema has increased, suggesting a gap in our understanding of the pathophysiology of this disease and insufficient crosstalk between clinical practice and preclinical research, which slows the development of innovative, personalized therapies. The recent trend towards less invasive treatments in advanced stage empyema opens new opportunities for pharmacological interventions. Its remarkable efficacy in pediatric empyema makes IPFT the first line treatment. Unfortunately, treatment approaches used in pediatrics cannot be extrapolated to empyema in adults, where there is a high level of failure in IPFT when treating advanced stage disease. The risk of bleeding complications and lack of effective low dose IPFT for patients with contraindications to surgery (up to 30%) promote a debate regarding the choice of fibrinolysin, its dosage and schedule. These challenges, which together with a lack of point of care diagnostics to personalize treatment of empyema, contribute to high (up to 20%) mortality in empyema in adults and should be addressed preclinically using validated animal models. Modern preclinical studies are delivering innovative solutions for evaluation and treatment of empyema in clinical practice: low dose, targeted treatments, novel biomarkers to predict IPFT success or failure, novel delivery methods such as encapsulating fibrinolysin in echogenic liposomal carriers to increase the half-life of plasminogen activator. Translational research focused on understanding the pathophysiological mechanisms that control 1) the transition from acute to advanced-stage, chronic empyema, and 2) differences in outcomes of IPFT between pediatric and adult patients, will identify new molecular targets in empyema. We believe that seamless bidirectional communication between those working at the bedside and the bench would result in novel personalized approaches to improve pharmacological treatment outcomes, thus widening the window for use of IPFT in adult patients with advanced stage empyema.